Jejunal gastrointestinal stromal tumor that developed in a patient with neurofibromatosis type 1: a case report - Hideki Nagano; Shigekazu Ohyama; Atsushi Sato; Jun Igarashi; Tomoko Yamamoto; Masumi Kadoya; Mikiko Kobayashi (BMC, 2023)
Abstract Background Neurofibromatosis type 1 (NF1) is known to be associated with the frequent occurrence of unique gastrointestinal stromal tumors (GISTs), preferably occurring in the small intestine, with no mutations in the c-kit proto-oncogene or platelet-derived growth factor receptor-alpha (PDGFRA), with a high tendency for multifocal development, indolent nature, with low proliferation activity and favorable prognosis. Case presentation A woman in her forties visited her local doctor complaining of menstrual pain; a large mass was detected in her lower abdomen, and she was referred to our hospital. The patient had hundreds of skin warts and café au lait spots. The patient's mother had been diagnosed with type 1 neurofibromatosis. The patient met the diagnostic criteria for NF1 and was diagnosed with NF1. Ultrasonography showed a large heterogeneous cystic mass with various echo patterns, solid compartments and multiple septations. Magnetic resonance imaging showed a multilocular cystic mass with liquid content exhibiting various intensities, including that of blood. A small round solid mass was also observed close to the cystic tumor. Contrast-enhanced computed tomography showed that the round solid mass showed strong enhancement in the early phase, unlike the cystic tumor component. Open laparotomy revealed a multicystic exophytic tumor measuring 11.5 cm originating from the jejunal wall, 20 cm distal to the duodenojejunal flexure. A solid tumor measuring 2.1 cm was also found on the anal side of the large tumor. We resected the short segment of the jejunum, including the two lesions. Microscopic findings revealed that the cystic and solid tumors consisted of spindle-shaped tumor cells showing little atypia with a fascicular or bundle arrangement. Nuclear mitosis was scarce. Immunostaining of the tumor cells showed positive staining for KIT and DOG1 and negative staining for S100 and desmin. The NF1 patient was diagnosed with multiple GISTs accompanied by intratumoral hemorrhagic denaturation arising from the jejunum. The TNM staging was pT4N0M0, stage IIIA. Conclusion We report a case of GISTs associated with NF1 that showed a jejunal origin, multifocal development and few mitotic figures. The recurrence risk, survival prognosis and need for adjuvant chemotherapy, particularly in cases where the initial GIST exhibits a very indolent pathology in NF1-related GISTs, remain to be elucidated.